2015
DOI: 10.1007/s12094-015-1342-7
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer and other second neoplasms after treatment of Hodgkin lymphoma

Abstract: RT treatment, especially with doses higher than 42 Gy, and smoking increase the risk of SN after HL. In this series, LC patients with early stages had a shorter elapsed time from HL diagnosis and longer OS, therefore the role of LC screening in HL survivors should be prospectively evaluated and smoking cessation counseling ought to be a key aspect during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Second, an increased incidence of skin and lung cancer is suggested to be related to exposure to radiotherapy, in particular in combination with systemic therapy [ 12 , 13 ]. This phenomenon is analogous to what has been observed among patients with Hodgkin lymphoma treated with radiotherapy [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 84%
“…Second, an increased incidence of skin and lung cancer is suggested to be related to exposure to radiotherapy, in particular in combination with systemic therapy [ 12 , 13 ]. This phenomenon is analogous to what has been observed among patients with Hodgkin lymphoma treated with radiotherapy [ 37 , 38 , 39 ].…”
Section: Discussionsupporting
confidence: 84%
“…Cigarette smoking increases second primary lung and tobacco‐associated cancer among survivors of Hodgkin lymphoma and cervical, breast, and urogenital cancers 23‐26 ; the elevated SMN risk in these survivors is likely due to the smoking prevalence 27 . Moreover, alcohol consumption and tobacco smoking heighten the risk of cancer in general 28 …”
Section: Discussionmentioning
confidence: 99%
“…Between the 1970s and 1990s, HL patients received extended-field radiation therapy (EFRT), which included mantle, extended mantle and subtotal nodal RT (figure 3). 5 It is well known that HL patients who have been treated with EFRT have an increased risk of developing subsequent malignancies 4 6–11. Several prospective studies have demonstrated that involved-field radiation therapy (IFRT) with 35 Gy RT for HL is as effective as EFRT with 35 Gy and reduces toxicities 12–14.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, chemotherapy and RT have dose-dependent and additive effects on the development of treatment-related lung cancer 11 19. Female patients who develop breast cancer as their treatment-related first primary malignancy have an increased risk of developing treatment-related second primary malignancies 6. Treatment-related lung cancers are diagnosed at either stage III or stage IV and are associated with poor outcomes 7 9.…”
Section: Discussionmentioning
confidence: 99%